Penggunaan Enzim Selulase-Hemiselulase pada Proses Deinking Kertas Koran Bekas - Jenni Rismijana; Iin Naomi Indriani; Tutus Pitriyani (Jurnal Matematika & Sains, 2003)
Deinking process of old newspaper by using cellulase-hemicellulase has been done. The old newspaper was beated, then at 4 % consistency, pH 5, and temperature 400 C, an enzyme was added with the dosage of 0,05-1,5 %. After reacting for 60 minutes the mixture was diluted and collector was added to catch the ink particles and then followed float for 20 minutes. The floating particle was scraped and the fibre was washed with fresh water until neutral pH and made as a sheet with 55 g/m2 grammage. A part of the fibre was bleached with peroxide before made as a sheet The optical and the physical properties including a dirt count, brightness, opacity, tensile index, tear index and elongation were tested. The experiment results showed the increase in the optical and the physical properties from the deinking sheet product. After bleaching process the optical properties increased, but the physical properties tended to decrease. The use of enzyme at 1% dosage gave the best result. The 0,05% enzyme dosage for the unbleached deiked pulp and 0,5% enzyme dosage for the bleached deiked pulp was able to fulfil the terms specification of newspaper according to SNI 14-0091-1998.